The diversification benefit of Islamic investment to Chinese conventional equity investors Evidence from the multivariate GARCH analysis - Saiti, Buerhan; Ma, Yusuf; Nagayev, Ruslan; Yumuşak, İbrahim Güran; Yumuşak, İbrahim Güran; Uluyol, Burhan (Emerald Group Publishing Ltd, 2020)
Purpose - The purpose of this paper is to investigate the extent to which Chinese equity investors can benefit from diversifying their portfolio into Shariah-compliant (Islamic) indices. It examines three Islamic stock indices (FTSE Shariah China price index, MSCI China Islamic IMI price index and the DJ Islamic Greater China price index) and ten sectoral indices in Shanghai Stock Exchange as a sample. Design/methodology/approach - The multivariate GARCH dynamic conditional correlations (MGARCH-DCC) is deployed to estimate the time-varying linkages of returns of the selected indices, covering approximately eight years daily data starting from 28 August 2009 to 29 September 2017. Findings - In general, in terms of volatility, the results indicate that all Islamic Indices are less volatile than the conventional indices. From the correlation analysis, the results imply that Chinese conventional equity investors would benefit from Islamic stock indices, especially when they include DJ Islamic Greater China in their portfolio. Originality/value - The findings of this paper may have several significant implications for the Chinese equity investors and fund managers for better understanding about co-movements of the Chinese conventional sectoral indices with the Shariah-compliant stock indices with the purpose of gaining higher risk-adjusted returns through portfolio diversification.
WOS:000531466800001
Keywords: Islamic finance; Portfolio selection; MGARCH; Islamic equity markets and indices equity markets; Chinese Islamic stock indices; Chinese sectoral indices; MGARCH; Portfolio diversification